Some considerations on the notion of analogy in Thomas Aquinas in the context of the problem of divine names - Vargas, Rosa Elvira (2020)
The paper offers an approximation to the Thomistic theory of the analogy of the divine names from a consideration of the general notion of analogy to which Aquinas subscribes and which has its origin on the discussions on equivocation found in logical treatises. It shows the extent to which the analogous predication of God and of creature is a unique case, not entirely equal to the traditional cases of analogous predication. The diverse ways in which Aquinas characterizes the analogy of the divine names would respond, not so much to an evolution of his thoughts on analogy, but to an attempt to characterize such difference.